2013
DOI: 10.1021/nl402875m
|View full text |Cite
|
Sign up to set email alerts
|

Local Strain Engineering in Atomically Thin MoS2

Abstract: Controlling the bandstructure through local-strain engineering is an exciting avenue for tailoring optoelectronic properties of materials at the nanoscale. Atomically thin materials are particularly well suited for this purpose because they can withstand extreme non-homogeneous deformations before rupture. Here, we study the effect of large localized strain in the electronic bandstructure of atomically thin MoS 2 . Using photoluminescence imaging, we observe a strain-induced reduction of the direct bandgap, an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

70
1,182
6
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,124 publications
(1,321 citation statements)
references
References 52 publications
70
1,182
6
6
Order By: Relevance
“…The corresponding difference in strain is estimated to be B0.2%. Although the DFT simulations do not account for the excitonic effects, the relative change of the calculated bandgap with respect to uniaxial strain ( À 44 meV per % strain) matches quite well with previous experiments on the PL peak position shift with strain ( À 45 meV per % strain 26 and À 36 meV per % strain 27 . Furthermore, as we mentioned, due to the fast cooling, a global tensile strain is found in MoS 2 .…”
Section: Resultssupporting
confidence: 83%
“…The corresponding difference in strain is estimated to be B0.2%. Although the DFT simulations do not account for the excitonic effects, the relative change of the calculated bandgap with respect to uniaxial strain ( À 44 meV per % strain) matches quite well with previous experiments on the PL peak position shift with strain ( À 45 meV per % strain 26 and À 36 meV per % strain 27 . Furthermore, as we mentioned, due to the fast cooling, a global tensile strain is found in MoS 2 .…”
Section: Resultssupporting
confidence: 83%
“…40 The result of Raman scattering modes is shown in Figure 3, where all the modes, not the resonant second order or combinations of first order modes, are shown in the It is known that the Raman E' peak of monolayer MoS2 is sensitive to strain and strain could induce a red-shift in the E' modes that have been observed for MoS2 monolayer or multilayers in other reports. 33,[41][42][43] The red-shift of the MoS2 E' peak after the two layers are coupled (thermally treated)…”
Section: Resultsmentioning
confidence: 99%
“…For example, significant energy redshifts of the near-band-edge (NBE) luminescence in uniaxial strain modulated ZnO [15] and GaAs [16] nanowires, as well as in curved ZnO [17][18][19][20] and CdS [21] micro/nanowires have been observed. It has also been reported that the elastic strain-gradient can effectively modulate the photoexcited carrier and exciton dynamics in MoS 2 atomic membrane [7,22] and ZnO micro/ nanowires [23,24].…”
Section: Introductionmentioning
confidence: 97%